Artificial Intelligent Based E- Health Monitoring Using Low Power Device in Wide Area Network - M. Monisha; P. Vijayalakshmi; V. Rajendran; D. Ravikumar (New Ideas Concerning Science and Technology Vol. 11, 2021)
In recent decades the health monitoring system extends with the new technology in International standards with funds in the poor countries. E-health monitoring lags in transferring the insufficient data security and huge medical records. The high power devices required for network function becomes the high cost devices. The limitation for the data insecurity, insufficient bandwidth and high power devices leads a way to the hybrid wide area network uses low power devices. The present work uses the E-Health monitoring system with devices working with low power in the hybrid large range network. The channel optimization algorithm controls the channel data rate and bandwidth. The optimization process enables the transmission for the medical records, which stored in database system. The medical records are transmitted based on the request from the patients and the doctor with the help of Artificial Intelligence (AI). The security system and their data base enables the security for e- health monitoring system. The proposed system improves in high speed, optimized data rate for medical data, low power devices. The system performance compared with the existing 3G e- health monitoring system.